Pembinaan instrumen saringan 'COMEL' untuk penilaian perkembangan kanak-kanak pra sekolah - Hashim, Nurul Ilyana (2018)
This study aims to devise, validate, and pilot a parent and teacher-rated instrument to screen developmental abilities of children aged 3 to 6 in Bahasa Malaysia. Extensive review was conducted to identify most important components in measuring children development and specific skills and abilities underneath each component (Study I). A series of expert panel evaluations were held to establish face, content, and construct validity (n=10), followed by predictive validity (n=30) (Study II). An initial study was conducted on 256 participants who rated children’s development as to establish the developed instrument’s reliability, feasibility, and to test related hypotheses. Five most important components in measuring children development was identified which are cognitive (C), vision (O), motor (M), emotion (E) and language (L) and communication abilities and was given an abbreviation as COMEL. Within each component, 12 items were initially constructed to tap children’s common developmental skills as they grow up from approximately 3 to 6 years old. A final version of validated and reliable COMEL consists of 72-items, arranged from simple to complex skills representing each component, written in simple sentence with accompanied coloured illustrations. For each skill the rated child has achieved, a Yes option is checked and 1 score obtained. Pearson correlation analysis found that the higher the developmental age of the child, the higher the scores in COMEL. Analysis of variances indicated that there were significant differences in scores of COMEL among children with different ages 3,4,5, and 6. Finally using Man Whitney test, we found there was no significant difference in scores of COMEL between boys and girls. COMEL is found to be a valid, reliable, feasible and useful instrument to screen children’s development around ages 3 to 6 years old.